TIME-MANAGEMENT AS A PEDAGOGICAL TECHNOLOGY OF STUDENTS’ EDUCATIONAL ACTIVITY - Tupchenko, V.; Ovcharenko , O. (Problems of Engineer-Pedagogical Education, 2023)
The article is devoted to the research of the problem of time management substantiation as a pedagogical technology of students’ educational activity. It is well known that in modern world higher education determines personal development and forms professional qualities of the individual, so it is very important to teach students to organize and plan their time. Time management can help organize academic activities and identify the most important goals and objectives. Researches define time management as a technology for organizing time and increasing efficiency of its use. It is a process of controlling the amount or time spent on certain activities in which efficiency and productivity purposefully increases. The search for answers to the challenges of modern world determined the problem of research, which is to define time management as a pedagogical technology that promotes development of students’ skills in educational activity at a higher education institution. The article considers the theoretical aspect of this problem, finds that there are a lot of definitions of the term “time management” in scientific literature, identifies the most common methods and provides their characteristics. Definitions of this concept from the point of view of both management and pedagogical science are analyzed. The article analyzes the concept of time management as a technology that helps perform various activities productively and efficiently with minimum amount of time spent. It is proved that the purpose of time management as a pedagogical technology is to teach students methods of educational activity self-organization and help in forming relevant skills which will increase the efficiency of the educational process and optimize it. It is proved in the article that time management has all the features of a pedagogical technology. The analysis of these features allowed determining the essence of time management as a pedagogical technology. The authors consider the essence of this concept, and its specific differences from the concept of “time management” in economics; its criteria and functions are defined. The research is based on a set of rules and procedures that contain a set of scientific, theoretical and empirical methods that are relevant to the goal and objectives and include integration of both quantitative and qualitative indicators study. The result of this work is reflected in the conclusion that time management as a pedagogical technology allows rationalizing students’ life time in relation to personal and educational goals and objectives. Time management is an axiological resource that improves quality of training and education. It is proposed in the article to organize special types of educational activity in which students will be able to master the basics of time management and use acquired skills in their further educational activity at a higher education institution.